Peran Strategi Pemasaran Digital UMKM Banten terhadap Loyalitas Pelanggan (Studi Case Apex Banten) - Rahma, Resita Septia; Ramdan, Abdi; Aditiya, Rizky; Siska, Siska; Ramdan, Gilang; Maulana, Alvin (Indonesian Scientific Journal, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, particularly in the Banten Province. This study focuses on Apex MSMEs in Banten, which operate in the outdoor equipment rental and tour trip organization business. In facing an increasingly competitive market, this study aims to analyze the marketing performance and customer loyalty of Apex MSMEs through digital marketing strategies. Data was collected through surveys using a Likert scale to measure customer loyalty. The results showed an average loyalty score of 4.521, indicating a high level of customer loyalty. SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats faced by Apex MSMEs. The resulting SO (Strengths-Opportunities) strategies included service and branch expansion and the use of social media for marketing. The findings provide valuable insights for Apex MSMEs in enhancing their competitiveness and business sustainability through appropriate marketing strategies. Thus, Apex MSMEs can strengthen their market position and achieve sustainable growth.